2020
DOI: 10.1111/jerd.12633
|View full text |Cite
|
Sign up to set email alerts
|

Methacrylate perspective in current dental practice

Abstract: Objective: To provide a current perspective concerning dental personnel sensitivity to methacrylate materials. Overview: Methacrylate related sensitivity and allergies are currently beyond traditional thoughts concerning denture base resins and methyl methacrylate provisional materials. Methacrylates are now ubiquitous in current dental practice and dental personnel should be aware that dental adhesives contain potent sensitizers that may also cross-sensitize individuals to other methacrylates not experienced.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 95 publications
0
14
0
Order By: Relevance
“…Such topical information (in any medial format) could be prepared under health pedagogical considerations and might be then presented within the framework of health education programs. This might also apply to other occupational fields for which relevant acrylate exposure has been evidenced in previous studies, such as dental personnel 68‐73 . The German Social Accident Insurance (DGUV) has recognized the problem for dental personnel and initially launched information brochures about acrylate allergy and its prevention.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Such topical information (in any medial format) could be prepared under health pedagogical considerations and might be then presented within the framework of health education programs. This might also apply to other occupational fields for which relevant acrylate exposure has been evidenced in previous studies, such as dental personnel 68‐73 . The German Social Accident Insurance (DGUV) has recognized the problem for dental personnel and initially launched information brochures about acrylate allergy and its prevention.…”
Section: Discussionmentioning
confidence: 97%
“…This might also apply to other occupational fields for which relevant acrylate exposure has been evidenced in previous studies, such as dental personnel. [68][69][70][71][72][73] The German Social Accident Insurance (DGUV) has recognized the problem for dental personnel and initially launched information brochures about acrylate allergy and its prevention. These existing informational materials might serve as a point of entry for developing potential awareness campaigns and future training measures tailored to the needs of workers in occupational groups exposed to acrylates.…”
Section: Discussionmentioning
confidence: 99%
“…Methacrylates are used as dental bonding agents and adhesives. A review of methacrylate‐associated ACD found a trend of increasing prevalence among dental professionals with 10% prevalence reported in 2004 and 20%–32%, in 2011 and 2013 1 . Furthermore, allergic cross‐reaction to one acrylic monomer, particularly HEMA, can lead to development of allergy to other monomers 2 …”
Section: Discussionmentioning
confidence: 99%
“…A review of methacrylate-associated ACD found a trend of increasing prevalence among dental professionals with 10% prevalence reported in 2004 and 20%-32%, in 2011 and 2013. 1 Furthermore, allergic cross-reaction to one acrylic monomer, particularly HEMA, can lead to development of allergy to other monomers. 2 Dentists may use a 'manual tray' for methacrylates-containing bonding agents.…”
Section: Discussionmentioning
confidence: 99%
“…PMMA denture base resins can trigger allergic contact dermatitis, such as type IV hypersensitivity or delayed reactions, in patients during prosthodontic procedures [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. The polymerization of methyl methacrylate (MMA) includes the addition of stabilizers such as hydroquinone and initiators such as dibenzoyl peroxide (BPO).…”
Section: Introductionmentioning
confidence: 99%